How, When and Why to Use Demand-Side Governance Approaches in Projects - Agarwal, Sanjay; Van Wicklin, Warren A., III (World Bank, Washington, DC, 2013)
This note offers a process-oriented guide to strengthening demand-side governance approaches in World Bank projects with a step-by-step approach for determining how demand for good governance (DFGG) tools and approaches can be applied to different types of Bank-funded projects. The objective of this note is to help task teams anticipate demand-side governance considerations early in the project preparation process, identify potential entry points for introducing DFGG tools to address these considerations, provide guidance on selecting DFGG tools which will improve governance, transparency and service delivery, assist borrowers to introduce DFGG tools in Bank projects, and to measure their impact. The core guidance is presented in the form of a simple five-step process for determining activity in a given project context. The annexes contain a glossary of DFGG tools, checklists, website links and other resources for task teams that will assist them in introducing and deepening DFGG work in Bank projects.